Protective coping: a grounded theory of educative interactions in palliative care nursing. - Morgan AK (International Journal of Palliative Nursing, 2001)
The development of a workable caring partnership in palliative care between the nurse, patient and informal carer is contingent upon the nurse's use of effective interactions that will not only inform, but also help individuals to work towards common beneficial goals. This article summarizes a research project undertaken in Western Australia, which examined the symbolic nature and characteristics of educative interactions. Their therapeutic value was interpreted in order to construct a theory, which in turn, explained their function. Protective coping, which deals with overcoming or minimizing stressors to the individual, has been identified as a basic social interactional process that is fundamental to the optimization of patients' well being during terminal illness care. An understanding of the knowledge-power relationship in palliative care is crucial if subsequent educative outcomes are to be positively influenced.